Assessment of the diagnostic efficacy of five non-invasive tests for MASLD: external validation utilizing data from two cohorts - Zou, Haoxuan; Pan, Wen; Sun, Xiaobin (Frontiers in Nutrition, 2025)
BackgroundNumerous non-invasive tests (NITs) have been developed for non-alcoholic fatty liver disease (NAFLD) over the past few decades. However, their applicability to metabolic-associated steatotic liver disease (MASLD), as redefined and renamed by the recent Delphi Consensus Statement, necessitates further investigation. Consequently, this study aims to systematically evaluate the diagnostic efficacy of five clinically utilized NITs (FLI/FSI/ZJU/LAP/HSI) in assessing the risk of MASLD.MethodsThe participants for this study were sourced from the Health Management Center at the Hospital of Chengdu Office of the Tibetan Autonomous Region, as well as from the National Health and Nutrition Examination Survey (NHANES) 2017–2020.3 cycle. The diagnostic efficacy of NITs was thoroughly evaluated and compared via methods such as the area under the curve (AUC), subgroup AUC, and clinical utility.ResultsThis study incorporated a total of 2,187 participants from the Health Management Center cohort and 5,524 participants from the NHANES cohort. In both cohorts, the FLI, FSI, LAP, ZJU, and HSI performed well in identifying those at high risk for MASLD. This effectiveness was consistently observed across various subgroups, including those defined by age, sex, race, overweight, hypertension, and diabetes status. Specifically, within the NHANES cohort, the FSI and FLI emerged as superior predictors of MASLD risk, with AUC values of 0.836 (95% CI: 0.826–0.847) and 0.835 (95% CI: 0.825–0.845), respectively. The difference in the AUC between these two NITs was not statistically significant (p > 0.05). In contrast, the ZJU, FLI, and FSI were more predictive of MASLD risk in the Health Management Center cohort. The AUC and 95% CI were: 0.815 (0.797–0.832), 0.810 (0.792–0.828), and 0.805 (0.787–0.823), respectively, and the difference in the AUC among them was not statistically significant (p > 0.05). The results remained the same when analyzed from the point of view of clinical utility, i.e., NRI, IDI, and DCA analyses were performed.ConclusionOverall, the FLI, FSI, ZJU, LAP, and HSI continue to demonstrate significant diagnostic value, even when they are applied to the newly designated MASLD and are suitable for screening in high-risk populations.